Digital Mind-Mapping to Improve Learners’ Grammar Competence - Afi Normawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2020)
Grammar has always been an important element of linguistic competence to be mastered in EFL contexts. The ways to teach and to make learners use grammar correctly have been the goals in grammar classes. This paper reports a study aimed at finding out if a grammar learning strategy called Digital Mind-Mapping (DMM) can improve learners’ grammar. The study was conducted in Universitas Nasional Karangturi Semarang involving first-semester students taking Words and Phrase Grammar (WPG) class. In the study, the researcher tried to discover the feasibility of DMM to be applied in grammar teaching and learning process since it involves the use of different platforms such as Instragram and WhatsApp in the learning processes. The study used a quantitative approach. The data were in the forms of students’ scores. They were collected by doing pre-test and post-test. Data analysis was carried out by using t-test. The findings show that DMM seems to have great potential to be used in grammar classes since it helps improve the students’ grammar. Keywords: Grammar, Mind-Map, Digital Mind-Mapping